2004
DOI: 10.1055/s-2004-820877
|View full text |Cite
|
Sign up to set email alerts
|

High‐Light Stress and Photoprotection in Umbilicaria antarctica Monitored by Chlorophyll Fluorescence Imaging and Changes in Zeaxanthin and Glutathione

Abstract: The effect of high light on spatial distribution of chlorophyll (Chl) fluorescence parameters over a lichen thallus (Umbilicaria antarctica) was investigated by imaging of Chl fluorescence parameters before and after exposure to high light (1500 micro mol m (-2) s (-1), 30 min at 5 degrees C). False colour images of F (V)/F (M) and Phi (II) distribution, taken over thallus with 0.1 mm (2) resolution, showed that maximum F (V)/F (M) and Phi (II) values were located close to the thallus centre. Minimum values we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
5
30
0
Order By: Relevance
“…For example, Mitrović et al (2011) and Stojanović et al (2010) reported the IC 50 values for methanolic extracts (45.57 lg/mL and 79.70 lg/mL), and reported the percentage of inhibition of DPPH radicals by methanolic (73.18%), acetone (60.18%) and aqueous (30.98%) extracts from H. physodes. Climatic conditions, such as high light intensity, high temperature and air pollution, have been shown to play important roles in the production of lichen metabolites and to influence their biological properties (Bartak et al 2004;Weissman et al 2006;Millot et al 2007). Thus, the biological properties of extract from the thalli of H. physodes grown in Poland may differ from those of H. physodes in other countries, where the lichen may be exposed to other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mitrović et al (2011) and Stojanović et al (2010) reported the IC 50 values for methanolic extracts (45.57 lg/mL and 79.70 lg/mL), and reported the percentage of inhibition of DPPH radicals by methanolic (73.18%), acetone (60.18%) and aqueous (30.98%) extracts from H. physodes. Climatic conditions, such as high light intensity, high temperature and air pollution, have been shown to play important roles in the production of lichen metabolites and to influence their biological properties (Bartak et al 2004;Weissman et al 2006;Millot et al 2007). Thus, the biological properties of extract from the thalli of H. physodes grown in Poland may differ from those of H. physodes in other countries, where the lichen may be exposed to other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that environmental factors play an important role in antioxidant activity of lichens. Extreme environmental factors such as high light, air pollution, desiccation, rehydration and high temperature affecting decreased antioxidant activity and reducing synthesis of antioxidants by lichens (Bartak et al 2004;Weissman et al 2005Weissman et al , 2006. Antioxidant activity of some other lichen was studied by other researchers.…”
Section: Correlations Between Total Phenolic Content and Antioxidativmentioning
confidence: 99%
“…Among them, formation of zeaxanthin during the initial phases of photoinhibition is well known (Demmig-Adams et al (1990b) and documented for number of chlorolichens from polar regions, e.g. Usnea antarctica (Barták et al 2003), Umbilicaria antarctica (Barták et al 2004). This effect, however, was not observed in cyanolichens.…”
Section: Introductionmentioning
confidence: 99%